A is 6 because so is the side across from it
And B is 8 because it the same size just flip it
Brainliest would be appreciated
Answer:
![\displaystyle \frac{x + 7}{3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bx%20%2B%207%7D%7B3%7D)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
- Terms/Coefficients
- Factoring
Step-by-step explanation:
<u>Step 1: Define</u>
<u />
<u />
<u />
<u>Step 2: Simplify</u>
- [Fraction] Factor numerator:
![\displaystyle \frac{(x + 5)(x + 7)}{3x + 15}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B%28x%20%2B%205%29%28x%20%2B%207%29%7D%7B3x%20%2B%2015%7D)
- [Fraction] Factor denominator:
![\displaystyle \frac{(x + 5)(x + 7)}{3(x + 5)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B%28x%20%2B%205%29%28x%20%2B%207%29%7D%7B3%28x%20%2B%205%29%7D)
- [Fraction] Divide:
![\displaystyle \frac{x + 7}{3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bx%20%2B%207%7D%7B3%7D)
Answer:
![12z^{2} -10z -12](https://tex.z-dn.net/?f=12z%5E%7B2%7D%20-10z%20-12)
Step-by-step explanation:
Let the number be z
2 more than 3 times z ==> 3z + 2
6 less than 4 times z ==> 4z - 6
Product of the above two is
![(3z + 2) (4z - 6) \\= (3z)(4z) + (3z)(-6) + (4z)(2) + (2)(-6)\\= 12z^{2} -18z + 8z - 12\\= 12z^{2} -10z -12](https://tex.z-dn.net/?f=%283z%20%2B%202%29%20%284z%20-%206%29%20%5C%5C%3D%20%283z%29%284z%29%20%2B%20%283z%29%28-6%29%20%2B%20%284z%29%282%29%20%2B%20%282%29%28-6%29%5C%5C%3D%2012z%5E%7B2%7D%20-18z%20%2B%208z%20-%2012%5C%5C%3D%2012z%5E%7B2%7D%20-10z%20-12)
In exponential form it is given as, 8⁻³ = ![$\frac{1}{512}](https://tex.z-dn.net/?f=%24%5Cfrac%7B1%7D%7B512%7D)
<u>Step-by-step explanation:</u>
We have to write the given equation in the exponential form, that is in the form of base to the power value.
Given:
log₈ (
) = -3
Here the base is 8.
In the exponential form, it is written as,
base to the power 3 = 512
Here the reciprocal of 512 is given, so,
base to the power -3 = ![$\frac{1}{512}](https://tex.z-dn.net/?f=%24%5Cfrac%7B1%7D%7B512%7D)
So the exponential form is given as, 8⁻³ = ![$\frac{1}{512}](https://tex.z-dn.net/?f=%24%5Cfrac%7B1%7D%7B512%7D)
Answer:
![2304 \ in^3](https://tex.z-dn.net/?f=2304%20%5C%20in%5E3)
Step-by-step explanation:
Given the surface dimensions of the garden as 24 inches by 48 inches:
#Calculate surface area of the garden's top:
![A=lw\\\\=48\times 24\\\\=1152 in^2](https://tex.z-dn.net/?f=A%3Dlw%5C%5C%5C%5C%3D48%5Ctimes%2024%5C%5C%5C%5C%3D1152%20in%5E2)
Given the soil's thickness is 2 Inches, we multiply this thickness by the garden's surface area to get volume of soil used:
![V=tA, t-thickness, A=Area=1152 \ in^2\\\\=2 \ in \times 1152\ in^2\\\\=2304 \ in^3](https://tex.z-dn.net/?f=V%3DtA%2C%20t-thickness%2C%20A%3DArea%3D1152%20%5C%20in%5E2%5C%5C%5C%5C%3D2%20%5C%20in%20%5Ctimes%201152%5C%20in%5E2%5C%5C%5C%5C%3D2304%20%5C%20in%5E3)
Hence, the amount of soil used is 2304 cubic inches.